MIX DESIGN WITH SYNTHETIC AND STEEL FIBERS IN THE MECHANICAL PROPERTIES OF CONCRETE - Chavarry Vallejos, Carlos Magno; De la Cruz Dueñas, Gustavo Gregorio; Ramírez Rondan, Raúl Neil; Zamora Terrones, Leydy Nataly; Pasos Sedano, Kelly Raquel; Diaz Scheering, Denise Nicole; Rosas Flores, Renato Alonso (LACCEI, 2025)
The research work focuses on the influence of synthetic fibers (FS) and metallic fibers (FM) when added to a concrete mixture with the purpose of improving its mechanical properties. There is a wide variety of fibers used to improve the quality of concrete such as steel fibers, glass, plastic and natural materials, which are available in various shapes, sizes and thicknesses. Each one has technical characteristics that are decisive for the study and will allow analyzing the mechanical properties of concrete without reinforcements compared to concrete reinforced with FS and FM in different dosages to improve the mechanical properties of the concrete. Three types of laboratory tests were carried out: compressive, flexural and tensile strength for different dosages of FM and/or FS (1%FM, 1%FS, 0.9%F.M + 0.1%FS, 0.825%FM + 0.175%FS , 0.75%FM + 0.25%FS), at the ages of 7, 14 and 28 days with a water-cement ratio (w/c) of 0.64, where cylindrical samples (specimens) and prismatic samples (beams) were made. It was determined that the optimal dosage of FM and F S is the one that has CP + 1% FM as its design, because it presents an improvement in the compression resistance by 1.07%, the flexural resistance increases by 82.61%. , tensile strength increases by 34.08% with respect to pattern concrete. Finally, it is concluded that the mechanical properties improve when a CP + 1%FM design is used because the resistance of the mechanical properties increases with respect to the master concrete (CP).